2017
DOI: 10.1016/j.jtusci.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Safety evaluation of green synthesizedCola nitidapod, seed and seed shell extract-mediated silver nanoparticles (AgNPs) using anAllium cepaassay

Abstract: Safety evaluation of green synthesized Colanitida pod, seed and seed shell extract-mediated silver nanoparticles (AgNPs) using an Alliumcepa assay,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 49 publications
3
19
0
Order By: Relevance
“…Table 1 summarizes the cytotoxic and genotoxic response registered after the exposure of Allium cepa to different concentrations of diverse AgNPs formulations from published data. Most of the formulations assessed reported cytotoxic and genotoxic damage, mainly those that lack of coating agent and the biogenically produced nanoparticles [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 summarizes the cytotoxic and genotoxic response registered after the exposure of Allium cepa to different concentrations of diverse AgNPs formulations from published data. Most of the formulations assessed reported cytotoxic and genotoxic damage, mainly those that lack of coating agent and the biogenically produced nanoparticles [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aside the pharmaceutical potentials of C. nitida, different parts of the plant have been employed as microbial substrate to produce enzyme and enhancement of nutritional qualities [ 27 , 28 ] and also for the synthesis of silver and silver-gold alloy nanoparticles [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ] for different biomedical and environmental applications. This work therefore seeks to extend the border of the potential applications of extracts of different parts of kola nut in nanobiotechnology.…”
Section: Introductionmentioning
confidence: 99%
“…These plant systems have been frequently used to study cytotoxic and genotoxic effects of nanoparticles on mitotic cell division and they have been considered as well model genetic system [ 32 ]. Yekeen et al [ 33 ] and Yekeen et al [ 34 ] have been reported that the cytotoxic effect of AgNPs on root meristems of Allium cepa used as a model of biological system. Hence, the present study was undertaken to investigate cytotoxic effect of silver nanoparticles on mitotic chromosomes of meristimetic root tip cells of D. polyantha .…”
Section: Introductionmentioning
confidence: 99%